AGRESI DA’I TERHADAP MAD’U DALAM KAJIAN PSIKOLOGI DAKWAH - Ahmad Ainun, Najib (ASWALALITA: Journal of Da'wah Management, 2022)
Abstrackt: This paper discusses the behavior of the Da’i who was identified as an act of aggression against mad'u, in the realm of psychology of course the act of aggression is not in accordance with what is taught by Islam. One form of aggression that occurs physically and verbally in the form of physical contact or words that are both painful for someone, The main purpose of this study is to examine the ideas and behavior of a preacher's aggression towards mad'u. The type of research used is a literature study or library research. a valid source of information related to the research discussion. The main method used in this study is the descriptive-analytical method, by describing the situation objectively psychologically, the study of the theory of aggression which has two important points in a person's personality, namely cognition and emotions that can control one's self in acts of aggression and stimuli that causes the stimulus to occur so that the background for the occurrence of aggression.